Excess conductivity and pseudogap state in YBa₂Cu₃-yAlyO₇₋δ single crystals with a system of undirectional twin boundaries - Vovk, R.V.; Obolenskii, M.A.; Bondarenko, A.V. (Functional Materials, 2007)
The conductivity in the basis plane of YBa₂Cu₃-yAlyO₇₋δ single crystals with a pre-specified topology of plane defects has been investigated. The results indicate that the doping with Al results in increased number of the effective scattering centers of the normal carriers. The excess conductivity for the analyzed single crystals within a wide temperature interval corresponds to an exponential temperature dependence. Near Tc, it is described well by the Aslamazov-Larkin theoretical model. A partial substitution of Cu with Al results in a considerable expansion of the temperature interval of pseudo-gap anomaly existence in the ab-plane.